Implementasi Wireless Sensor Node Sebagai Pendukung Pertanian Modern Berbasis Pemrograman State Machine - Rivaldi Wibowo; Sabriansyah Rizqika Akbar; Bayu Priyambadha (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
At this time, the monitoring system conducted by farmers still using manual procedures, namely to check directly to the field. At the time of manual checking can occur error at the time of input data such as writing errors due to the number of data. From these problems, it is necessary that the system periodically checks on the state of the plant. Therefore WSN is used as a means of checking wirelessly to facilitate the monitoring of plants and state machine methods used as a method used in research. In this research used several sensors, among others, temperature sensors, light sensors, and soil sensors. In this research the state machine method is used as a useful method to see the behavior of systems that have been made by researchers. Tests on the system made done as much as 6 times that is ,times the test on the execution of each state, testing the length of transition execution, testing the total state execution time and transition, sensor testing, data delivery testing, and sleep mode test. So the result of the implementation of state machine method successfully done with the system running. In this Research the average results of state testing as much as 10 times the total state station transition is state â€œdiamâ€ 21543.6 microsecond, state â€œtermonitorâ€ 921594.4 microsecond, and â€œterkirimâ€ 1161218.4 microsecond. Then the results of the tested sensors in accordance with the expected and incoming data in accordance with the display serial monitor. For sleep mode test is not in accordance with the settings that have been done due to a delay factor in the program that affects the of the system becomes longer than the time specified.